BAHASA INGGRIS - Dayang Suriani (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2020)
This study is directed to obtain information how peer feedback can improve students’ ability in writing. Specifically, it is directed to investigate whether peer feedback works and can improve students’ writing ability in writing sentences and narrative paragraphs, at the first year students of SMA Negeri 1 Balikpapan. The study was conducted based on the result of preliminary study at the school. It is found that the students’ ability in the language skills especially in writing is still insufficient. In the teaching and learning process the teacher provides fewer portions in writing activities for the students in class. In addition, the strategies used in the teaching and learning process are uninteresting because the students have to do the writing activities in under pressure. To answer the problems, a classroom action research is conducted. The teacher as a researcher works in planning the action, implementing the action, observing, and analyzing and reflecting the action. The subjects of the study are the second year students (X-IPA-1) of 2019/2020 academic year consisting of 40 students. The results shows that peer feedback obviously can improve the students’ ability in writing sentences and narrative paragraphs at the first year students of SMA Negeri 1 Balikpapan. It has been observed that the improvements are caused by the regular writing practice done by the students and the teacher’s response given to their writing. It becomes a sort of on going dialogue.